Dissecting the role of the CXCL12/CXCR4 axis in acute myeloid leukaemia. (5th March 2020) - Ladikou, Eleni E; Chevassut, Timothy; Pepper, Chris J; Pepper, Andrea GS
Summary: Acute myeloid leukaemia (AML) is the most common adult acute leukaemia with the lowest survival rate. It is characterised by a build‐up of immature myeloid cells anchored in the protective niche of the bone marrow (BM) microenvironment. The CXCL12/CXCR4 axis is central to the pathogenesis of AML as it has fundamental control over AML cell adhesion into the protective BM niche, adaptation to the hypoxic environment, cellular migration and survival. High levels of CXCR4 expression are associated with poor relapse‐free and overall survival. The CXCR4 ligand, CXCL12 (SDF‐1), is expressed by multiple cells types in the BM, facilitating the adhesion and survival of the malignant clone. Blocking the CXCL12/CXCR4 axis is an attractive therapeutic strategy providing a 'multi‐hit' therapy that both prevents essential survival signals and releases the AML cells from the BM into the circulation. Once out of the protective niche of the BM they would be more susceptible to destruction by conventional chemotherapeutic drugs. In this review, we disentangle the diverse roles of the CXCL12/CXCR4 axis in AML. We then describe multiple CXCR4 inhibitors, including small molecules, peptides, or monoclonal antibodies, which have been developed to date and their progress in pre‐clinical and clinical trials. Finally, the review leads us to the conclusion that there is a need for further investigation into the development of a 'multi‐hit' therapy that targets several signalling pathways related to AML cell adhesion and maintenance in the BM.